2001
DOI: 10.1080/10550490150504128
|View full text |Cite
|
Sign up to set email alerts
|

Liver Diseases by Alcohol and Hepatitis C: Early Detection and New Insights in Pathogenesis Lead to Improved Treatment

Abstract: Much progress has been made in the understanding of the pathogenesis of alcoholic liver disease, resulting in improvement of treatment. Therapy must include correction of nutritional deficiencies, while taking into account changes of nutritional requirements. Methionine is normally activated to S-adenosylmethionine (SAMe). However, in liver disease, the corresponding enzyme is depressed. The resulting deficiencies can be attenuated by the administration of SAMe but not by methionine. Similarly, phosphatidyleth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 128 publications
(135 reference statements)
1
8
0
1
Order By: Relevance
“…[3][4][5] A similar observation has been found among obese patients with hepatic steatosis. These investigators also found that steatosis was observed more commonly in association with genotype 3 independent of body mass index.…”
supporting
confidence: 69%
“…[3][4][5] A similar observation has been found among obese patients with hepatic steatosis. These investigators also found that steatosis was observed more commonly in association with genotype 3 independent of body mass index.…”
supporting
confidence: 69%
“…Alcohol is a drug that depresses the central nervous system like sedative and anesthetics. It is not a stimulant as widely believed but speech becomes free and social inhibition may be forgotten since it affects the portion of the brain that control judgment (Leiber, 2000). It infiltrates the brain, liver heart, pancrease, lung and kidney within minutes and passes into the blood stream (Epstein, 1992).…”
Section: Intoductionmentioning
confidence: 99%
“…Finally, it is important to better understand how outcomes related to AOD use may differ across racial/ethnic groups. Although research has shown that non-whites often have worse health outcomes (Caetano & Clark, 1998; Herd, 1989; Lieber, 2001; NIDA, 1998; Stinson, Grant, & Dufour, 2001; Sutocky, Shultz, & Kizer, 1993) and more problems (e.g., with family, accidents) associated with AOD use compared to whites (Galvan & Caetano, 2003) even with less AOD use, it is not clear why this occurs (NIAAA, 2002). …”
mentioning
confidence: 99%